Randomised trial of planned caesarean section prior to versus after 39 weeks: unscheduled deliveries and facility logistics--a secondary analysis. - Julie Glavind; Tine Brink Henriksen; Sara Fevre Kindberg; Niels Uldbjerg (PLoS ONE)
Objectives To compare the impact of scheduling caesarean section prior to versus after 39 completed weeks of gestation on the occurrence of unscheduled caesarean section and rescheduling of the procedure. Methods Secondary analysis from a multicentre randomised open-label trial including singleton pregnant women with a healthy foetus and a reliable due date. Women were allocated by computerized telephone randomisation to planned caesarean section at 38 weeks and three days or 39 weeks and three days. The outcomes were unscheduled deliveries with provided reasons, such as spontaneous labour onset or supervening complications, and any changes in the scheduled delivery date. Statistical analyses were according to intention-to-treat using Fisher's exact test. Results From March 2009 to June 2011 1,274 women were included. Median difference in gestational age at delivery was six days. Compared to the 38 weeks group, the women in the 39 weeks group were more likely to have an unscheduled caesarean section (15.2% vs. 9.3%; RR 1.64, 95% CI 1.21; 2.22), to deliver between 6 pm and 8 am (10 % vs. 6%; RR 1.68, 95% CI 1.14; 2.47), or to have the procedure rescheduled (36.7% vs. 23%; RR 1.6, 95% CI 1.34;1.90). Conclusions Scheduling caesarean section after 39 weeks leads to a 60% increase in unscheduled caesarean sections and a 70% increase in delivery outside regular work hours as compared to scheduling of the procedure prior to 39 weeks. Trial registration www.clinicaltrials.gov NCT00835003 http://www.clinicaltrials.gov/ct2/show/NCT00835003?term=NCT00835003&rank=1.